Adapting Nanotech Research as Nano-Micro Hybrids Approach Biological Complexity, A Review. Issue 5 (May 2016) - Vongehr, Sascha; Tang, Shaochun; Meng, Xiangkang
Abstract : Today's emergence of nano-micro hybrid structures with almost biological complexity is of fundamental interest. Our ability to adapt intelligently to the challenges has ramifications all the way from fundamentally changing research itself, over applications critical to future survival, to posing globally existential dangers. Touching on specific issues such as how complexity relates to the catalytic prowess of multi-metal compounds, we discuss the increasingly urgent issues in nanotechnology also very generally and guided by the motto ' Bio Is Nature's Nanotech '. Technology belongs to macro-evolution; for example integration with artificial intelligence (AI) is inevitable. Darwinian adaptation manifests as integration of complexity, and awareness of this helps in developing adaptable research methods that can find use across a wide range of research. The second half of this work reviews a diverse range of projects which all benefited from 'playful' programming aimed at dealing with complexity. The main purpose of reviewing them is to show how such projects benefit from and fit in with the general, philosophical approach, proving the relevance of the 'big picture' where it is usually disregarded.